Remembering the Gulf: changes to the marine communities of the Sea of Cortez since the Steinbeck and Ricketts expedition of 1940. Issue 7 (1st September 2008) - Sagarin, Raphael D; Gilly, William F; Baxter, Charles H; Burnett, Nancy; Christensen, Jon
Abstract : One of the most storied biological expeditions is the 1940 trip to the Sea of Cortez (Gulf of California) by author John Steinbeck and his close friend Edward F Ricketts, a professional biologist. Steinbeck and Ricketts visited intertidal sites around the Gulf and made extensive collections, taking notes on fauna and natural history. In 2004, we retraced the Steinbeck and Ricketts voyage, visiting the same intertidal sites during the same season and using the authors' extensive natural history notes as a baseline for comparison. Although we found many of the same species as they did, populations were, in many cases, not as geographically widespread, and individuals were fewer in number and smaller in size. In particular, echinoderms and large gastropods showed declines, as did most large pelagic vertebrate species. One of the most remarkable changes in the pelagic community is the present abundance of jumbo squid, Dosidicus gigas, a species not reported in 1940. Although Steinbeck and Ricketts, by their own admission, "could not yet relate the microcosm of the Gulf with the macrocosm of the sea", the changes we observed with historical perspective are in agreement with documented changes in ocean and coastal ecosystems around the world.